Educational and Anthropological Perspectives: An Italian View on Migration in Multi-cultural Urban Spaces - Patrizia Panarello (Social Work & Society, 2008)
In contemporary societies there are different ways to perceive the relation between identity and alterity and to describe the difference between "us" and "them", residents and foreigners. Anthropologist Sandra Wallman sustains that in multi-cultural urban spaces the frontiers of diversity are not only burdensome markers of identity, but rather they could also represent new chances to define "identity" and "alterity". These frontiers, in fact, can work like interfaces through which to build time after time, in a creative way, a relationship with the other. From this point of view, the concept of boundary can offer many opportunities to creatively define the relation with the other and to sign new options for cognitive and physical movement. On the other side, in many cases we have a plenty of mechanisms of exclusion that transforms a purely empirical distinction between "us" and "them" in an ontological contrast, as in the case when the immigrant undergoes hostilities through discriminatory language. Even though these forms of racism are undoubtedly objectionable from a theoretical point of view, they are anyway socially "real", in the sense that they are perpetually reaffirmed and strengthened in public opinion. They are in fact implicit "truths", realities that are considered objective, common opinions that are part of day-to-day existence. That is the reason why an anthropological prospective including the study of "common sense" should be adopted in our present day studies on migration, as pointed out by American anthropologist Michael Herzfeld. My primary goal is to analyze with such a critical approach same pre-conditions of racism and exclusion in contemporary multi-cultural urban spaces. On the other hand, this essay would also investigate positive strategies of comparing, interchanging, and negotiating alterity in social work. I suggest that this approach can offer positive solutions in coping with "diversity" and in working out policies for recognizing a common identity which, at the same time, do not throw away the relevance of political and economic power.